Usage evaluation of the physiotherapy evidence database (PEDro) among Brazilian physical therapists - Elkins, Mark R.; Moseley, Anne M.; Pinto, Rafael Z. [UNESP] (FapUNIFESP (SciELO), 2015)
Background: It is unclear whether the Physiotherapy Evidence Database (PEDro) is widely and equally used by physical therapists in Brazil. As PEDro is considered a key resource to support evidence-based physical therapy, analyses of PEDro usage could reflect the extent of dissemination of evidence-based practice. Objective: To describe the usage of PEDro among the five regions of the World Confederation for Physical Therapy (WCPT) and, in more detail, in the South American region and Brazil over a 5-year period. Method: PEDro home-page sessions and the number of searches performed were logged for a 5-year period (2010-2014). Absolute usage and relative usage were calculated for each region of the WCPT, each country in the South American region of WCPT, and each Regional Council (CREFITO) in Brazil. Results: Europe had the highest absolute and relative usage among the five regions of the WCPT (971 searches per million-population per year), with the South American region ranked 4th in absolute terms and 3rd in relative terms (486). Within the South American region, Brazil accounted for nearly 60% of searches (755). Analysis at a national level revealed that usage per physical therapist in Brazil is very low across all CREFITOs. The highest usage occurred in CREFITO 6 with 1.3 searches per physical therapist per year. Conclusions: PEDro is not widely and equally used throughout Brazil. Strategies to promote PEDro and to make PEDro more accessible to physical therapists speaking Portuguese are needed.
Keywords: Evidence-based practice; Physical therapy; Rehabilitation